PENERAPAN TEKNOLOGI SILASE RANSUM KOMPLIT DALAM UPAYA MENGATASI KEKURANGAN PAKAN PADA MUSIM KEMARAU DI DUSUN GELIANG DESA PEMPATAN - I.G.L.O. Cakra; B.R.T. Putri; I.K. Budaarsa; N.M.S. Sukmawati; A.A.P.P. Wibawa (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2018)
Pempatan village located at 600-1100 m altitude with annual rainfall average 2000-2500 mm and minimumtemperature 270C and maximum 360C. Generally, the basic livelihood of the Pempatan villagers is fromcattle livestock. Forage production in the dry season is very low and tend to shortage of forage, while in therainy season is excess of forage. The feeding only from fresh forage, where the existence of forage depend onthe season, so in the dry season generally shortage of forage and could decrease the cattle productivity. Basedon the problems it is necessary to explanation about technology of complete ration of silage to effort theshortage of feed in the dry season at Geliang, Pempatan Village. The community services activity attend by25 people, 16 people from the breeder, and the rest from the students. Based on the results of communityservices activity and interviews with the livestock groups found that Geliang Lestari group has potential todevelop, it could be seen from the seriousness of the participants to attend the community services and thefeed demonstrations with well understood and accepted. In this activity, was introduced complete rationsilage and demonstrated the offering for cattle. Based on the results of the community services activity, itcould be concluded that bali cattle is possible for developing in Geliang Lestari Sustainable Livestock Group.The development of the livestock population must be followed by supplies of feed through the processingand storage in complete ration silage.